2019
DOI: 10.1016/j.bandl.2019.104692
|View full text |Cite
|
Sign up to set email alerts
|

Brain-behavior relationships in incidental learning of non-native phonetic categories

Abstract: Research has implicated the left inferior frontal gyrus (LIFG) in mapping acousticphonetic input to sound category representations, both in native speech perception and non-native phonetic category learning. At issue is whether this sensitivity reflects access to phonetic category information per se or to explicit category labels, the latter often being required by experimental procedures. The current study employed an incidental learning paradigm designed to increase sensitivity to a difficult non-native phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Lim et al (2019) recognized that participants were able to incidentally learn auditory categories during videogame play without direct attention to them, the striatum was engaged during this practice, and the control of striatal activity and connectivity differed in both experimental and control groups, which evidenced the sensitivity of the striatal learning system. The results of both Luthra et al (2019) and Lim et al (2019) confirmed the efficacy of incidental learning at the level of brain functions that emphasizes the viability of this method as means of vocabulary acquisition. All of these studies showed that the use of incidental learning among ELLs is an effective approach when acquiring new L2 vocabulary.…”
Section: Figure 2 Comparison Among Modes Of Vocabulary Acquisitionsupporting
confidence: 56%
See 1 more Smart Citation
“…Lim et al (2019) recognized that participants were able to incidentally learn auditory categories during videogame play without direct attention to them, the striatum was engaged during this practice, and the control of striatal activity and connectivity differed in both experimental and control groups, which evidenced the sensitivity of the striatal learning system. The results of both Luthra et al (2019) and Lim et al (2019) confirmed the efficacy of incidental learning at the level of brain functions that emphasizes the viability of this method as means of vocabulary acquisition. All of these studies showed that the use of incidental learning among ELLs is an effective approach when acquiring new L2 vocabulary.…”
Section: Figure 2 Comparison Among Modes Of Vocabulary Acquisitionsupporting
confidence: 56%
“…However, inquiries involved in neuroscience attempt to shed light on the efficacy of incidental learning when this experience is not monitored. For example, a study analyzing the neuroscientific explanation of incidental learning among students showed that during this practice, frontal lobe parts of the brain are engaged after learning (Luthra et al, 2019). The study used functional MRI scans that linked the ability to retain novel phonetic category information to the function of frontal brain regions, even when students were not provided explicit category labels (Luthra et al, 2019).…”
Section: Figure 2 Comparison Among Modes Of Vocabulary Acquisitionmentioning
confidence: 99%
“…While adults require some amount of feedback to learn (Chandrasekaran et al, 2015;Chandrasekaran, Yi, et al, 2014;Lim & Holt, 2011;McClelland et al, 2002;Tricomi et al, 2006;Yi et al, 2016), adults can acquire speech categories incidentally (Y. Gabay et al, 2015;Lim et al, 2019;Luthra et al, 2019) or with task-irrelevant feedback (Goudbeek et al, 2008;McClelland et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we assume learning only occurs during overt training. Instead, implicit learning experiments suggest that categorization performance can improve through training without explicit knowledge of the categorical structure (Luthra et al, 2019). However, our results indicate that categorization responses exhibit the greatest change during training where feedback on the interval category is present (Fig.…”
Section: Discussionmentioning
confidence: 56%